2020
DOI: 10.1093/sleep/zsaa123
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and tolerability of lemborexant compared with placebo in adults with insomnia disorder: results from the phase 3 randomized clinical trial SUNRISE 2

Abstract: Abstract Study Objectives To assess long-term efficacy and safety of lemborexant (LEM), a novel dual orexin receptor antagonist, versus placebo in adults with insomnia disorder. Methods This was a 12-month, global, multicenter, randomized, double-blind, parallel-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
134
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 113 publications
(158 citation statements)
references
References 32 publications
14
134
0
Order By: Relevance
“…Consistent with findings from other Phase 1 clinical studies 9 and Studies 303 and 304, 7,8 lemborexant was found to be well tolerated in the current Phase 1 study. In conclusion, the results from these analyses indicate that lemborexant can be coadministered with ARAs (H 2 antagonists, PPIs, and antacids) and does not warrant dose modifications, which is supported by the lack of restrictive language in the US and Japanese prescribing information.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with findings from other Phase 1 clinical studies 9 and Studies 303 and 304, 7,8 lemborexant was found to be well tolerated in the current Phase 1 study. In conclusion, the results from these analyses indicate that lemborexant can be coadministered with ARAs (H 2 antagonists, PPIs, and antacids) and does not warrant dose modifications, which is supported by the lack of restrictive language in the US and Japanese prescribing information.…”
Section: Discussionsupporting
confidence: 90%
“…gastric acid, insomnia, lemborexant, orexin receptor antagonists, pharmacokinetics placebo at 1 month (Study 304) and through 12 months (Study 303), and was well tolerated. 7,8 Lemborexant is a Biopharmaceutics Classification System Class II molecule and exhibits pH-dependent solubility. Specifically, in vitro dissolution studies have shown that lemborexant exhibits delayed dissolution in weak acid and neutral conditions compared with dissolution at lower pH ( Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…The superiority of lemborexant, 5 mg and 10 mg, compared with placebo was demonstrated by significant improvements in sSOL, sSEF, sWASO, and sTST during the initial week of the treatment period that remained significant at the end of the 6-month placebo-controlled period (Table 3 1,10 ). At the end of 6 months, there were significantly more sleeponset responders and sleep-maintenance…”
Section: Clinical Pointmentioning
confidence: 99%
“…• Sunrise 1, a 4-week trial with older adults that included laboratory polysomnography (PSG) studies (objective) and patient-reported sleep measures (subjective) on selected nights 9 • Sunrise 2, a 6-month trial assessing patient-reported sleep characteristics in adults and older adults. 10 Sunrise 1 was performed with older adults with insomnia who were randomized to groups with nightly use of lemborexant,…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation